2019
DOI: 10.1186/s12888-019-2366-2
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction test: Croatian preliminary study

Abstract: BackgroundEveryday internet usage is particularly significant in the population of adolescents and young people. Besides numerous benefits, internet usage brings certain risks of addictive behavior. Internet Addiction Test (IAT) is the most spread scale for measuring internet addiction. The aim of this study was to investigate internet addiction on a sample of Croatian adolescents.MethodsOverall, 352 students aged between 15 and 20 from randomly selected high schools participated in the study. We have collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
30
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 41 publications
6
30
2
6
Order By: Relevance
“…The CIAS cutoff score of 63/64 [ 39 ] indicated a 24.4% (95% confidence interval, 21.8–27.0%) IA prevalence in the examined sample. The prevalence rate appears to be higher than those found in previous researches regarding middle school student samples, including Kawabe et al’s [ 52 ] Japan junior high school student sample (2.0%; aged 12–15 years), Stavropoulos, Alexandraki, & Motti-Stefanidi’s [ 53 ] Greek high school student sample (3.1%; mean age 16), Černja et al’s [ 54 ] Croatia high school student sample (3.4%; aged between 15 and 20), Liu et al’s [ 55 ] USA high school student sample (4.0%; age range = 14–18 years), Kuss et al’s [ 56 ] Netherlands adolescents (3.7%; Mage = 14.2, SD = 1.1 years), Park et al’s [ 57 ] South Korean middle and high school student sample (10.7%), Sasmaz et al’s [ 58 ] high school student sample in Turkey (15.1%; mean age was 16.1 ± 0.9 years), Lau et al’s [ 59 ] Hong Kong secondary school student sample (16.0%; mean age = 14.53 years), Tan et al’s [ 60 ] China junior high school student sample (17.2%), Lin et al’s [ 13 ] Taiwan senior high school student sample (17.4%; Mage = 15.83, SD = 0.38 years), and Di Nicola et al’s [ 61 ] Italy high school student sample (22.1%; mean age was 16.47 ± 4.85 years). The prevalence rate of IA appears to vary within a wide range of middle school students, however, the prevalence rate of IA in this study was observed to be the highest.…”
Section: Discussioncontrasting
confidence: 57%
“…The CIAS cutoff score of 63/64 [ 39 ] indicated a 24.4% (95% confidence interval, 21.8–27.0%) IA prevalence in the examined sample. The prevalence rate appears to be higher than those found in previous researches regarding middle school student samples, including Kawabe et al’s [ 52 ] Japan junior high school student sample (2.0%; aged 12–15 years), Stavropoulos, Alexandraki, & Motti-Stefanidi’s [ 53 ] Greek high school student sample (3.1%; mean age 16), Černja et al’s [ 54 ] Croatia high school student sample (3.4%; aged between 15 and 20), Liu et al’s [ 55 ] USA high school student sample (4.0%; age range = 14–18 years), Kuss et al’s [ 56 ] Netherlands adolescents (3.7%; Mage = 14.2, SD = 1.1 years), Park et al’s [ 57 ] South Korean middle and high school student sample (10.7%), Sasmaz et al’s [ 58 ] high school student sample in Turkey (15.1%; mean age was 16.1 ± 0.9 years), Lau et al’s [ 59 ] Hong Kong secondary school student sample (16.0%; mean age = 14.53 years), Tan et al’s [ 60 ] China junior high school student sample (17.2%), Lin et al’s [ 13 ] Taiwan senior high school student sample (17.4%; Mage = 15.83, SD = 0.38 years), and Di Nicola et al’s [ 61 ] Italy high school student sample (22.1%; mean age was 16.47 ± 4.85 years). The prevalence rate of IA appears to vary within a wide range of middle school students, however, the prevalence rate of IA in this study was observed to be the highest.…”
Section: Discussioncontrasting
confidence: 57%
“…Results in a study conducted in Germany also manifested such results [22]. Studies in Italy, UK, Finland, India, Croatia, Germany, China, Saudi Arabia and USA also proved the same results on these three factorial dimensions like in current study [20,22,35,36,37]. The outcomes of current study should be envisaged for its recommendations and disadvantages if any must be addressed for onward research.…”
Section: Discussionsupporting
confidence: 81%
“…This study was aimed to assess the internet addiction level in medical students of Bolan University of Medical and Health Sciences Pakistan since can said to be one of the detailed prelude study in the country. Simultaneously this 34,35] explained with the factor structural dimensions as did in current study. The results of this study have almost the same outcomes seen in Chinese study.…”
Section: Discussionsupporting
confidence: 79%
“…U nekoliko istraživanja iz različitih evropskih zemalja dobiveni su slični rezultati. Naučnici iz Hrvatske (Černja, Vejmelka & Rajter, 2019) su proveli istraživanje pomoću IAT-a na uzorku od 352 mladih (od 15 do 20 godina starosti), te su zaključili da je 3,4% mladih izrazito ovisno o internetu, dok je oko 35% ispitanih pokazalo nekoliko znakova ovisnosti. Istraživanje provedeno u Italiji upotrebom istog testa pokazalo je da 9% (od 200 ispitanika) mladih ima potencijal da razvije internet ovisnost, a da 68% mladih provodi veoma mnogo vremena online (Iannitelli et al, 2018).…”
Section: Ovisnost Mladih U Bosni I Hercegovini O Internetuunclassified